A stakeholder perspective on social stability risk of public–private partnerships project for water environmental governance in China: A social network analysis - Wang, Wenke; Guo, Xinlin; Cao, Qilin; Tang, Aomei (Frontiers in Ecology and Evolution, 2023)
The pluralism of stakeholders in PPP project for water environmental governance and the complex interrelationship among stakeholders are the important factors affecting social stability risk. Previous studies have mainly focused on risk identification and assessment. We aim to investigate the key social risks of PPP project for water environmental governance, to understand which social risks stakeholders are concerned about, and what interactions they follow. First, relevant risks and their interrelationships were investigated through a literature review and interviews. Second, the key social stability risks were identified based on social network analysis. Third, strategies were proposed to mitigate the social stability risks. The results show that government corruption, government intervention risk, approved risk, poor contract design risk price change and policy and regulation risk are the key risks with the highest in/out-degree, centrality and ego network size. Four core stakeholder groups (i.e., government, contractors, project companies, and the public and the media) and four core challenges (i.e., difficulties in financing, lack of mass incidents prevention mechanism, incomplete project schedule control system and improper handling of benefit compensation issues) have intensive relationships. We concluded that controlling the complicated relationships among four core stakeholder groups can reduce the social stability risks. The social network analysis framework combining stakeholder management and risk management provides a reference for the management of PPP projects for water environmental governance.